Television in the age of radio : modernity, imagination, and the making of a medium - Sewell, Philip W., 1970- (Rutgers University Press, 2013)
Television in the Age of Radio is a unique account of how television came to be, not just from technical innovations or institutional struggles, but from cultural concerns that were central to the rise of industrial modernity. A major revision of the history of television, it provides investigations of the values of early television amateurs and enthusiasts, the passions and worries about competing technologies, and the ambitions for programming that together helped mold the medium.